The Relationship between Emotional Intelligence and Marketing Effectiveness and its Impact on Market Spread (Loyalty, Product Positioning and Mental Image) For Multi-national Companies - Abdel Halim, Eman (The Arab Journal of Administration, 2021)
This paper investigates the relationship between emotional intelligence of executive managers in multinational companies and marketing effectiveness, highlighting the dimensional marketing growth in developing and developed countries alike. Will loyalty of consumers to the product remain the same when moving between countries – given the fact that the mental image and market position of the product vary between different markets. Multi-stage random sampling used in this study and the research sample was calculated using percentage (n = 158). The results of this research uncovered a positive correlation between variables of emotional intelligence, specially self-management and self-awareness of executive managers, and all the variables of marketing effectiveness. It also asserted a positive correlation between all variables of emotional intelligence and marketing effectiveness – with a higher influence of marketing effectiveness variables on customer loyalty, product position and mental image.